IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN A PROBLEM-BASED LEARNING MODEL - Yunisa Aulia; Dadang Dahlan; Hana Mardiati Dahlan (Nurul Jadid University, 2024)
The aim of this research is to determine the extent to which students' learning outcomes have improved through the application of differentiated learning in a Problem-Based Learning (PBL) model in the Economics subject. The study employs a action research, consisting of two cycles, beginning with a pre-cycle. Each cycle includes the stages of planning, implementing, observing, and reflecting. The results of the research indicate an improvement in students' affective learning outcomes, with pre-cycle data showing 85% (good category), Cycle I showing 82% (good category), and Cycle II showing 88% (very good category). Psychomotor learning outcomes also showed an increase, starting from 78% in the pre-cycle (good category), rising to 82% in Cycle I (good category), and reaching 86% in Cycle II (very good category). Cognitive learning outcomes demonstrated significant improvement as well, with pre-cycle average scores at 57 (10 students achieving the passing grade, 28%), Cycle I average scores at 77 (26 students achieving the passing grade, 72%), and Cycle II average scores at 86 (31 students achieving the passing grade, 86%). The research demonstrates that the implementation of differentiated learning within a Problem-Based Learning model effectively enhances student learning outcomes in the Economics subject.